2014
DOI: 10.1016/j.pathophys.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor (HB-EGF) therapy for intestinal injury: Application and future prospects

Abstract: Throughout the past 20 years, we have been investigating the potential therapeutic roles of heparin-binding EGF-like growth factor (HB-EGF), a member of the epidermal growth factor family, in various models of intestinal injury including necrotizing enterocolitis (NEC), intestinal ischemia/reperfusion (I/R) injury, and hemorrhagic shock and resuscitation (HS/R). Our studies have demonstrated that HB-EGF acts as an effective mitogen, a restitution-inducing reagent, a cellular trophic factor, an anti-apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…Heparin-binding EGF-like growth factor has been identified as a biologic agent capable of preventing NEC in various animal models and of reversing the effects of established NEC, via positive effects on mucosal healing 135 , intestinal stem cell function 136 and vascular perfusion 84,137 . A readily absorbed and nontoxic oligosaccharide that inhibits TLR4 was shown to prevent NEC in mice and piglets and to reduce intestinal inflammation in ex vivo human intestine obtained during the treatment of NEC 68 .…”
Section: Strategies For Nec Preventionmentioning
confidence: 99%
“…Heparin-binding EGF-like growth factor has been identified as a biologic agent capable of preventing NEC in various animal models and of reversing the effects of established NEC, via positive effects on mucosal healing 135 , intestinal stem cell function 136 and vascular perfusion 84,137 . A readily absorbed and nontoxic oligosaccharide that inhibits TLR4 was shown to prevent NEC in mice and piglets and to reduce intestinal inflammation in ex vivo human intestine obtained during the treatment of NEC 68 .…”
Section: Strategies For Nec Preventionmentioning
confidence: 99%
“…As a member of the EGF family, HB-EGF binds to the EGF receptor (EGFR) and has known mitogenic effects. HB-EGF is expressed in response to hypoxia, tissue damage, and oxidative stress, including in the intestine, and has a pivotal role in tissue regeneration and repair [31,32]. In seeking to evaluate the role of exogenous HB-EGF in the context of NEC, Dvorak and colleagues demonstrated that either the oral administration of HB-EGF or EGF significantly reduced NEC in a premature rat model through increased production of MUC2, a secretory mucin [33].…”
Section: Heparin-binding Epidermal Growth Factormentioning
confidence: 99%
“…Most of its distribution shortly after administration is within the plasma, liver, kidneys, bile, and urine. (Feng et al, 2006, Yang et al, 2014) The rapid decline of HB-EGF in plasma is dues to a rapid irreversible uptake process. (Burwen et al, 1985, Dunn and Hubbard, 1984, Kim et al, 1988, St Hilaire et al, 1983)Given its rapid distribution and elimination, it is not surprising that the small doses used in our study, even if delivered intravenously, cannot be detected above background levels.…”
Section: Discussionmentioning
confidence: 99%